'The blue dot thing': a discourse analysis of learner interlanguage in instructional design. Issue 2 (3rd April 2022) - Howard, Craig D.; L. Bevins, Katherine
ABSTRACT: We used audio-recorded interactions from a co-design of early designers working together making a language learning app to map discourse practices onto an operationalisation of an early stage of design learning in instructional design. A previously published typography of design discourse operationally defined the discourse practices of an advanced beginner stage. We asked, How did the discourse practices of early designers emerge when they engaged each other in the act of designing? We searched transcripts for examples of nine discourse practices in design that were previously established by the literature which suggested these discursive practices might appear in design language in use. We found that these practices often did appear, but ranged in discursive proficiency, suggesting the existence of an interlanguage of design. This discourse analysis informs scholars of design learning as to the variability in the emergence of discourse practices in design. To illustrate these insights, we present five diverse excerpts that illuminate the breadth of how design discourse emerges in early designer's discussions. From these data, we concluded that there is an interlanguage of instructional design that maps unevenly across discourse practices of the advanced beginner.